Perancangan Enterprise Architecture Planning Menggunakan Zachman Framework Pada PT. Palma Abadi - Widjaja, Calvinia Flora; Assegaff, Setiawan (Jurnal Manajemen Sistem Informasi, 2021)
PT. Palma Abadi is a company engaged in the management of palm oil to palm oil and core, with the status of PMDN (Domestic Investment). One of the obstacles faced by PT. Palma Abadi is a difficult information system integration in every part of the company. To deal with these problems, companies must implement enterprise architecture planning. Enterprise architecture design will use the Zachman framework method, the goal is to get a clear picture of how to design an enterprise architecture and how to get a good enterprise architecture that can be used by organizations to achieve its strategic goals.